Risk Factors Associated With Abnormal Urinalysis in Children - Zhong, Xuhui; Ding, Jie; Wang, Zheng; Gao, Yan; Wu, Yubin; Shen, Ying; Song, Hongmei; Zhao, Zhengyan; Chen, Xinxin; Zhang, Puhong; Xu, Guobin; Yao, Chen; et al. (Frontiers in Pediatrics, 2021)
Background: Targeted urinalysis has been suggested to improve screening efficiency in adults. However, there is no well-defined target population in children yet, with limited information on the risk factors for urinalysis abnormalities. Methods: Children from infants to 17 years old were randomly selected. Dipstick urinalysis was initially performed. Among those who were abnormal, a repeat dipstick or dipstick with microscopic urinalysis was performed for confirmation. Results: In total, 70,822 children were included, with 37,866 boys and 32,956 girls. Prevalence of abnormal urinalysis was 4.3%. Age was significantly associated with abnormal urinalysis, with the highest prevalence among 12–14-year-olds. Girls were 2.0 times more likely to exhibit abnormalities. Compared with children whose guardians had a college degree or higher, those whose guardians had a high school degree or lower had a higher likelihood of abnormalities. Geographic location was also associated with abnormal results. Conclusion: Girls, children aged 12–14 years old, and children whose guardians had a low educational level and children in certain geographic locations were significantly associated with abnormal urinalysis. Identification of children at high risk would contribute to targeted urinalysis screening.